Optimalisasi Pasir Kuarsa Lokal Sebagai Material Proppant dalam Hydraulic Fracturing Studi Edukatif di SMK Migas Bumi Melayu Riau - Novrianti Novrianti; Richa Melysa; Selvi Harvia Santri; M Tegar Satria P; Leo Edoardo P (PELANTAR PRESS, 2026)
This Community Service Program (PKM) aims to enhance students’ understanding and skills in hydraulic fracturing technology at SMK Migas Bumi Melayu Riau, with a particular focus on proppant materials and reservoir permeability. The partner institution faces challenges related to limited hands-on learning opportunities and a lack of instructional materials that integrate oil and gas concepts with local resources. Riau Province has abundant quartz sand resources, which were utilized in this program as an educational medium to support vocational learning. The program was implemented using an educational and participatory approach that included lectures, interactive discussions, and the introduction of local quartz sand as a simulation material for proppants used in hydraulic fracturing. The activity was conducted on December 12, 2025, at SMK Migas Bumi Melayu Riau and involved students from the Oil and Natural Gas Production Engineering program. The results demonstrated an improvement in students’ understanding of the fundamental concepts of hydraulic fracturing and the role of proppants, as well as an increased interest in the utilization of local resources for oil and gas applications. The program also produced learning modules and educational media that can be used sustainably by the partner institution to support future instructional activities. Overall, this PKM program contributes to strengthening vocational education based on regional potential and supports the development of skilled young human resources who are better prepared to meet the challenges of the oil and gas industry.